Recycling of Plastic Waste and Scrap Tires to Prepare Insulating Materials - Abbas, Shaban; Abbas, Maram (Latakia University Journal -Basic Sciences Series, 2018)
Plastic and rubber products considered of being a great importance to humans, but their residues and wastes are a real environmental disaster. They are dumped in fields, streams and forests or buried in large landfills that pose a serious hazard that needs to work on solve it in the best possible way. On the other hand, the economic problems caused by the erosion of concrete cement have made it the major problem of infrastructure in the industrialized countries. Over the past three decades, this problem has reached alarming proportions, which led to high repair costs, whether in concrete or in reinforcing steel, Especially acidic media due to concrete permeability of acid rainwater, where these costs exceeded initial construction amounts in some cases. This paper deals with the recycling of used tires and some types of plastic waste to be used in the preparation of insulating materials for water and heat at a low cost compared to the insulation materials currently used in the construction process, in addition to the preparation of floor tiles for internal and external use.